99mTc Radiolabeling and Biological Evaluation of Nanoparticles Functionalized with a Versatile Coating Ligand. Issue 16 (12th March 2015) - Felber, Michael; Bauwens, Matthias; Mateos, José M.; Imstepf, Sebastian; Mottaghy, Felix M.; Alberto, Roger
Abstract Radiolabeling allows noninvasive imaging by single photon emission computed tomography (SPECT) or positron emission tomography (PET) for assessing the biodistribution of nanostructures. Herein, the synthesis of a new coating ligand for gold nanoparticles (AuNPs) and quantum dots (QDs) is reported. This ligand is multifunctional; it combines the metal chelate with conjugating functions to biological vectors. The concept allows the coupling of any targeting function to the chelator; an example for the prostate specific membrane antigen is given. Derivatized NPs can directly be labeled in one step with [99mTc(OH2)3(CO)3]+. AuNPs in particular are highly stable, a prerequisite for in vivo studies excluding misinterpretation of the biodistribution data. AuNPs with differing sizes (7 and 14 nm core diameter) were administered intravenously into nude NMRI mice bearing LNCaP xenografts. MicroSPECT images show for both probes rapid clearance from the blood pool through the hepatobiliary pathway. The 7 nm AuNPs revealed a significantly higher bone uptake than the 14 nm AuNPs. The high affinity towards bone mineral is further confirmed in vitro with hydroxyapatite.